Structure and function of the septum nasi and the underlying tension chord in crocodylians. Issue 1 (10th November 2015) - Klenner, Sebastian; Witzel, Ulrich; Paris, Frank; Distler, Claudia
Abstract: A long rostrum has distinct advantages for prey capture in an aquatic or semi‐aquatic environment but at the same time poses severe problems concerning stability during biting. We here investigate the role of the septum nasi of brevirostrine crocodilians for load‐absorption during mastication. Histologically, both the septum nasi and the septum interorbitale consist of hyaline cartilage and therefore mainly resist compression. However, we identified a strand of tissue extending longitudinally below the septum nasi that is characterized by a high content of collagenous and elastic fibers and could therefore resist tensile stresses. This strand of tissue is connected with the m. pterygoideus anterior. Two‐dimensional finite element modeling shows that minimization of bending in the crocodilian skull can only be achieved if tensile stresses are counteracted by a strand of tissue. We propose that the newly identified strand of tissue acts as an active tension chord necessary for stabilizing the long rostrum of crocodilians during biting by transforming the high bending stress of the rostrum into moderate compressive stress.